PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN DI PUSKESMAS MAKRAYU PALEMBANG - Ismandra (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2020)
The purpose of this study was to determine and analyze the effect of service quality on patient satisfaction at Makrayu Health Center Palembang. The population in this study were people who live in the work area of ​​the Makrayu Health Center and have provided health services at the Makrayu Health Center with a total sample of 100 respondents who were selected using the Simple Random Sampling technique. Primary data collection using a questionnaire and secondary data collection using literature study. Hypothesis testing in this study used multiple linear regression analysis with a significance value of a = 5% (0.05). The results showed that physical evidence, empathy, assurance, responsiveness, and reliability simultaneously had a positive and significant effect on patient satisfaction. Partially reliability and empathy have a positive and significant effect on patient satisfaction. Meanwhile, responsiveness, assurance, and physical evidence have a positive and insignificant effect on community satisfaction as a patient. The Adjusted R Square value obtained through testing the Determinant Coefficient (R2) is 0.341, which means that 34.1% of patient satisfaction as the dependent variable can be explained by the independent variable, namely service quality, while the remaining 65.9% can be explained by other variables not examined in this study.